Eastern Caribbean Currency Union : Staff Report for the 2005 Regional Discussions. (IMF Staff Country Reports; Country Report ;, 2005)
This 2005 Article IV Consultation highlights that economic activity in the Eastern Caribbean Currency Union (ECCU) has accelerated since mid-2003 owing to an acceleration of activity in the tourism and construction sectors. Inflation has been stable and monetary aggregates have been expanding rapidly, reflecting continued growth in the demand for money and confidence in the banking system and the quasi-currency board arrangement. Against this background, Executive Directors have called for strengthening fiscal consolidation, lowering the debt ratios, and ensuring the consistency of fiscal policies with the currency board arrangement.